A Multicenter Study Evaluating the Risk Factors and Outcomes of Repeat Descemet Stripping Endothelial Keratoplasty. Issue 2 (February 2019) - Thompson, Jordan M.; Truong, Alexander H.; Stern, Hudson D.; Djalilian, Ali; Cortina, M. Soledad; Tu, Elmer Y.; Johnson, Paula; Verdier, David D.; Rafol, Lorene; Lubeck, David; Spektor, Tatyana; Jorgensen, Colin; et al.
Abstract : Purpose: Descemet stripping endothelial keratoplasty (DSEK), currently the most common procedure for managing corneal endothelial dysfunction, may be repeated following DSEK failure from a variety of causes. This multicenter study reports the risk factors and outcomes of repeat DSEK. Methods: This was an institutional review board-approved multicenter retrospective chart review of patients who underwent repeat DSEK. Twelve surgeons from 5 Midwest academic centers and 3 private practice groups participated. The Eversight Eye Bank provided clinical indication and donor graft data. We also assessed the role of the learning curve by comparing cohorts from the first and second 5-year periods. Results: A total of 121 eyes from 121 patients who underwent repeat DSEK were identified. The average age of the patients was 70 ± 12 years. The most common indication for repeat DSEK was late endothelial graft failure without rejection (58%, N = 63). Average preoperative and 12-month postoperative repeat DSEK corrected distance visual acuities were 20/694 and 20/89, respectively. Visual acuity outcomes, endothelial cell density, and cell loss did not significantly vary between the 2 cohorts. Initial graft rebubble rates for the first and second cohorts were 51% and 25%. The presence of glaucoma, prior glaucoma surgery, or a history of penetrating (full thickness) keratoplasty did not significantly affect visual outcomes. The median, mean, and range of intraocular pressures before repeat DSEK were 15.0, 15.7, and 6 to 37 mm Hg, respectively. Patients with higher intraocular pressures before repeat DSEK had improved postoperative corrected distance visual acuities. Conclusions: Repeating DSEK improves vision following failed or decompensated DSEK surgery. Higher preoperative repeat DSEK IOPs were associated with improved visual outcomes, and initial graft rebubble rates, which decreased over time, were likely due to surgeon experience. Abstract : Supplemental Digital Content is Available in the Text.